2008
DOI: 10.1038/nature07405
|View full text |Cite
|
Sign up to set email alerts
|

The ectodomain of Toll-like receptor 9 is cleaved to generate a functional receptor

Abstract: Mammalian Toll-like receptors (TLRs) 3, 7, 8 and 9 initiate immune responses to infection by recognizing microbial nucleic acids1, 2; however, these responses come at the cost of potential autoimmunity due to inappropriate recognition of self nucleic acid3. The localization of TLR9 and TLR7 to intracellular compartments appears to play a role in facilitating responses to viral nucleic acids while maintaining tolerance to self nucleic acid, yet the cell biology regulating the trafficking and localization of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
668
8
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 540 publications
(713 citation statements)
references
References 23 publications
34
668
8
3
Order By: Relevance
“…However, as IL‐1β and IL‐18 were both undetectable in culture supernatants from Rnaseh2b −/− cells (data not shown), an inflammasome‐mediated response was unlikely. While the observed ISG induction would be consistent with TLR9 activation, signalling is impaired by deficient proteolytic processing of the receptor in MEFs (Ewald et al , 2008), and we therefore prioritised assessment of the cGAS‐STING pathway. We performed siRNA depletion of cGAS in Rnaseh2b −/− MEFs and found that cGAS depletion significantly abrogated the ISG response and CCL5 production (Fig 4A).…”
Section: Resultsmentioning
confidence: 95%
“…However, as IL‐1β and IL‐18 were both undetectable in culture supernatants from Rnaseh2b −/− cells (data not shown), an inflammasome‐mediated response was unlikely. While the observed ISG induction would be consistent with TLR9 activation, signalling is impaired by deficient proteolytic processing of the receptor in MEFs (Ewald et al , 2008), and we therefore prioritised assessment of the cGAS‐STING pathway. We performed siRNA depletion of cGAS in Rnaseh2b −/− MEFs and found that cGAS depletion significantly abrogated the ISG response and CCL5 production (Fig 4A).…”
Section: Resultsmentioning
confidence: 95%
“…Asagiri et al, reported that chemical or genetic ablation of cathepsin K attenuated inflammatory autoimmune disease apparently via a marked reduction in TLR9-induced signalling leading to the production of . Three recent studies confirmed a requirement for endosomal proteolysis in TLR9 signalling and went further by showing that a key protease target is TLR9 itself [1,2,94]. Apparently, cleavage in the extracellular domain of TLR9 increases binding of CpG containing oligonucleotides and crucially, cleaved TLR9 recruited the signalling adaptor MyD88 much more efficiently than intact TLR9 [1].…”
Section: Tlr Signallingmentioning
confidence: 94%
“…Whether proteolysis of the other nucleic acid-sensing TLR is required is not yet clear. In the studies mentioned above, one demonstrated that TLR7 proteolysis occurred [1], but no cleavage of TLR7 was detected in another study [2].…”
Section: Tlr Signallingmentioning
confidence: 97%
See 2 more Smart Citations